Achitectural research of mausoleum Khozha Akhmed Yassawi in Turkestan - Мәлібекұлы, Жандарбек (Рroblems of engineering and professional education, 2025)
This article examines the development of architectural research The mausoleum of Khozha Akhmed Yassawi in Turkistan in the 20th century. The history of Kazakhstan`s architecture began with studies of the Khozha Akhmed Yassawi mausoleum in Turkistan. This monument became the focus of almost all the developments in architectural studies.